If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(7x + 3) = 236 Reorder the terms: 4(3 + 7x) = 236 (3 * 4 + 7x * 4) = 236 (12 + 28x) = 236 Solving 12 + 28x = 236 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 28x = 236 + -12 Combine like terms: 12 + -12 = 0 0 + 28x = 236 + -12 28x = 236 + -12 Combine like terms: 236 + -12 = 224 28x = 224 Divide each side by '28'. x = 8 Simplifying x = 8
| 6x^2+25x+75=0 | | 2x^2+25x+75=0 | | 1/5-1/7 | | 5(8-6x)=-140 | | 5x^2+20x+75=0 | | 0*x=1/2 | | 5x^2+25x+75=0 | | 2e^3x=8 | | 4x^2+25x+120=0 | | 4x^2+14x+120=0 | | n(10n+8)=0 | | 4x^2+14+120=0 | | 2z+5=11 | | 4x^2+14+107=0 | | z=X/y | | 4(4+5)+3=35 | | 4x^2+12+86=0 | | 1/2-4/9 | | .5b+7=10 | | 3x^2+12+86=0 | | 21x^2+14x/7x | | 1/4(2x-2)=8 | | 3x^2+55+215=0 | | 12x+4(x-2)=1607 | | 9x-7=2-5x | | 3x^2+55+225=0 | | 3x^2+100+225=0 | | 4x^2+100+225=0 | | 5x^2+100+225=0 | | 5x^2+71+443=0 | | 6x+15=16x+4 | | =1607 |